Association between parents’ body height with stunting in children ages 1-5 years old in Nagi Primary Health Care Working Area Larantuka City, East Flores, Indonesia - Wega Upendra Sindhughosa; I Made Arimbawa (DiscoverSys Inc., 2020)
Background: Parents' body height is one factor associated with stunting incidence in the child. In under-five years old children, the body height is influenced by genetic factors and the environment during development periods. Short mothers are one of the factor that related to the incidence of stunting. This study aims to determine the associations of parents' body height with stunting in children age 1-5 years old in Nagi Primary Health Care working area, Larantuka City. Methods: A cross-sectional study was conducted among 123 children age 1-5 years old who met the inclusion criteria were included in this study at Nagi Primary Health Care, Larantuka City. Data was taken from primary data and questionnaire distributed that consist of 3 main parts contains research sample characteristics, father's body height, and mother's body height. Chi-square is used to analyze the relationship between the father's body height and mother's body height with stunting. All of the data were analyzed using SPSS version 17 for Windows.Results: Most of the respondents were female (53.7%), followed by having a normal body height (67.5%), normal body weight (97.6%), >155 cm of mother's body height (65.0%), and >165 cm of father's body height (62.6%). In bivariate analysis, there is no relationship between father's body height with stunting (p>0.01), but statistically significant between mother's body height with stunting (p<0.01). In addition, a moderate positive correlation was found between Mid-Parental Height (MPH) with the children body weight (r=0.41; p=0.01).Conclusion: Mother's body height had a significant association with stunting incidence. In addition, the MPH also had a moderate positive correlation to the children body height.